Andrzej Pągowski jako autor plakatów filmowych - Kornacki, Krzysztof (Załącznik Kulturoznawczy, 2024)
Andrzej Pągowski claims that he does not like to repeat himself and each poster he creates is different – apart from repetitive workshop elements such as central composition or lettering at the top. Meanwhile, if we compare Pągowski’s posters side by side, we will notice their thematic and problematic repetition. This is not easy to achieve in poster art for two reasons: the thematic and stylistic differences of the illustrated films and the practical function of the poster. In the Polish People's Republic, the latter was not that important. Pągowski himself took care of the former, preferring strong representational elements (aggressive in reception, like in Eisenstein's work) and reaching for recurring motifs that create his own specific anthropology. Most often, it employs the motif of a face or an animal muzzle. Often, what is human and what is animal becomes intertwined with each other, because the foundations of Pągowski’s anthropology lie in biologism, naturalism and Freudianism. At the same time, Pągowski places the objects on the posters in an aesthetic key of surrealism, grotesque and macabre. If the poster is treated as an intersemiotic translation (in media, of course, ontologically quite distant from each other), then the three aspects of the translation can be distinguished: plot, form (genre, style) and meanings. Thus, it would be difficult, first of all, to guess the theme or plot of the film from many of Pągowski’s posters. Secondly, many posters do not provide any suggestion whatsoever as to the genre and style of the film, or they hint at it incorrectly. Thirdly, the meaning of the poster is either unclear or distant from the meanings of the screen original and exposes the above-mentioned anthropology of the creator. It can be said that Pągowski is an “authoritarian author”.